Turkish _German Relations (1923-1945) - Hanna Azzo Behnan (دراسات أقليمية, 2010)
This research explain the nature of political & economic relations between Turkey & Germany since establishment of the Turkish Republic in 1923 until the end of World War 11. These relations developed and continued until the first years of the war, which Turkey deduced from the two struggle sides (the alliance and axis states) in exporting the chrome metal, that is necessary in military industries, because of its neutral attitude, but by the increasing pressures of the alliance on Turkey caused break off its diplomatic relations with Germany in August, 1944, which was followed by another step of war declaration on Germany in February 1945.